Secondary particle lithium manganese iron phosphate positive electrode material, preparation method thereof and battery
By introducing conductive oxides and fast ion conductor materials into lithium manganese iron phosphate, the secondary particle structure and optimized coating are solved, and the problem of low tap density of lithium manganese iron phosphate is significantly improved, which has significantly improved its electron conduction and lithium ion conduction Performance improves the energy density of the battery.
Patent Information
- Application Number
- CN202411447628.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-03
AI Technical Summary
The low tap density of lithium manganese iron phosphate material leads to insufficient energy density in batteries, and existing modification methods have failed to fundamentally solve this problem.
By adding tubular or sheet-like conductive oxides and graphite materials in the preparation process of lithium manganese phosphate, a conductive network is established, and a rod-like or sheet-like fast ion conductor material is used to form a secondary particle structure to reduce hygroscopicity And increase the compaction density, while optionally adding carbon sources for surface coating.
It significantly improves the electron conduction and lithium ion conduction properties of lithium manganese iron phosphate, enhances the stability and compaction density of the material, and improves the electrochemical performance of the battery.
Smart Images

Figure CN119252914A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of energy materials, and in particular relates to a secondary particle lithium manganese iron phosphate positive electrode material and a preparation method, and a battery. Background Art
[0002] At present, lithium manganese iron oxide has low electronic conductivity, low lithium ion diffusion coefficient, and Mn 3+ The Jahn-Teller effect and other shortcomings limit its large-scale application. Common modification methods include particle size nano-sizing and morphology control, conductive phase carbon coating and ion doping. At present, the lithium manganese iron phosphate on the market is mainly a primary particle material, and the particle size is 1-2μm to achieve good conductivity and lithium ion transmission performance. In this way, the specific surface area of the material is large, and a high content of carbon coating is required to achieve good electronic conductivity, which leads to low compaction density of the material and poor processing performance due to moisture absorption. For example, the application with publication number CN103762362A discloses a hydrothermal preparation method of a nano-lithium manganese iron phosphate positive electrode material, which uses a hydrothermal method and a spray drying method to prepare a titanium-doped lithium manganese phosphate positive electrode material. The method uses a one-step hydrothermal synthesis composite material, which is easy to cause a large consumption of lithium source. And although carbon coating can improve the electronic conductivity of the surface of the material particles of lithium manganese iron phosphate, since the conductivity of lithium manganese iron phosphate is lower than that of lithium iron phosphate, the amount of carbon coating needs to be larger to better exert the electrochemical properties of lithium manganese iron phosphate. However, since the carbon coated on the surface of lithium iron manganese phosphate is mainly an amorphous loose structure, the tap density of the coated lithium iron manganese phosphate and the compaction density of the electrode film are greatly reduced. Ultimately, the energy density of lithium iron manganese phosphate batteries has no obvious advantage over traditional lithium iron phosphate batteries. And the application with publication number CN109250698B discloses a method for preparing a lithium iron manganese phosphate positive electrode material with a high tap density, which uses small-particle lithium iron manganese phosphate with a particle size of 0.3-0.8μm and large-particle lithium iron manganese phosphate with a particle size of 3-5μm to mix in a mass ratio to achieve the purpose of increasing the tap density. However, this method does not fundamentally solve the problem of low tap density of lithium iron manganese phosphate. It is therefore urgent to propose a new modified lithium iron manganese phosphate positive electrode material. Summary of the invention
[0003] The present application provides a secondary particle lithium manganese iron phosphate positive electrode material and a preparation method thereof, and a battery, which aims to solve the problem of low energy density of lithium iron phosphate batteries caused by low tap density of lithium manganese iron phosphate to a certain extent.
[0004] In a first aspect, the present application provides a method for preparing a secondary particle lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0005] S1, mixing a lithium source, an iron source, a manganese source, a phosphorus source and a dispersant to obtain a first mixed slurry;
[0006] S2, mixing the first mixed slurry with the conductive material and the fast ion conductor, adding water, grinding, and spray drying to obtain a spherical precursor;
[0007] S3, adding the spherical precursor to a carbon source for calcination and sieving to obtain a secondary particle manganese iron phosphate lithium positive electrode material.
[0008] The present application adds tubular or lamellar conductive oxides or graphite materials during the preparation of secondary particle lithium iron manganese phosphate positive electrode materials, establishes a conductive network in the secondary particles of lithium iron manganese phosphate, and improves the electronic conductivity inside the secondary particles. The lithium ion conductivity inside the secondary particles can be effectively improved by adding rod-shaped or lamellar fast ion conductor materials. The secondary particles are spherical in shape formed by the agglomeration of small nano-sized particles (primary particles). Compared with the primary particles of lithium iron manganese phosphate, the secondary particles have a larger particle size, a smaller specific surface area, and reduced surface contact with air and adsorption, which reduces moisture absorption and other problems during the processing of the positive electrode slurry and improves the stability of the material. At the same time, the dense secondary spherical particles can effectively increase the compaction density of lithium iron manganese phosphate.
[0009] A small amount of carbon source is added to coat the surface of the secondary spherical particles with carbon to improve the conductivity of the entire secondary spherical surface. It is also possible not to add a carbon source.
[0010] In the second aspect, the present application provides a secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method of the first aspect, the molecular formula of which is LiMn x Fe 1-x PO4 (x=0.4, 0.45, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9), particle size D50 is 1μm-15μm, and is formed by the agglomeration of nanoscale primary particles.
[0011] In a third aspect, a lithium manganese iron phosphate battery comprises the secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method described in the first scheme, or the secondary particle lithium manganese iron phosphate positive electrode material described in the second aspect.
[0012] It can be understood that the beneficial effects of the second to third aspects mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0014] Figure 1 The crystal structure diffraction pattern of the secondary particle lithium manganese iron phosphate positive electrode material prepared in Example 1;
[0015] Figure 2 This is a scanning electron microscope image of the secondary particle lithium manganese iron phosphate positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0017] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0018] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0019] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0021] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0022] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0023] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0024] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0025] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0026] In a first aspect, a method for preparing a secondary particle lithium manganese iron phosphate positive electrode material is provided, comprising the following steps:
[0027] S1, mixing a lithium source, an iron source, a manganese source, a phosphorus source and a dispersant to obtain a first mixed slurry;
[0028] S2, mixing the first mixed slurry with the conductive material and the fast ion conductor, adding water, grinding, and spray drying to obtain a spherical precursor;
[0029] S3, adding the spherical precursor to a carbon source for calcination and sieving to obtain a secondary particle manganese iron phosphate lithium positive electrode material.
[0030] In some embodiments, the lithium source package in step S1 is a combination of at least one or more of lithium hydroxide, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate and dilithium hydrogen phosphate; the iron source includes a combination of at least one or more of iron phosphate, iron sulfate, iron nitrate, iron oxalate and iron acetate; the manganese source includes a combination of at least one or more of manganese phosphate, manganese sulfate, manganese nitrate, manganese oxalate and manganese acetate; the phosphorus source includes a combination of at least one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and dilithium hydrogen phosphate.
[0031] In some embodiments, the conductive material in step S1 is a lamellar, rod-shaped, tubular or granular material of at least one or more combinations of graphite, graphene, carbon nanotubes, aluminum-doped zinc oxide, fluorine-doped tin dioxide and antimony-doped tin dioxide; the fast ion conductor material is a lamellar, rod-shaped, tubular or granular material of at least one or more combinations of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium phosphate, lithium aluminum silicate, lithium phosphorus oxynitride, sodium fast ion conductor material and lithium aluminate.
[0032] In some embodiments, the dispersant in step S1 is a combination of one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol and citric acid, and the amount of the dispersant added is 1wt% to 20wt% of the sum of the mass of the lithium source, manganese source, iron source and phosphorus source; the element molar ratio of the raw material added in step S1 is lithium: manganese: iron: phosphorus: oxygen = 1: x: (1-x): 1: 4, 0.4 <x<1。
[0033] In some embodiments, the mass of the conductive material in step S2 is 0.1wt% to 2wt% of the sum of the masses of the lithium source, manganese source, iron source, and phosphorus source, and the mass of the fast ion conductor is 0.1wt% to 2wt% of the sum of the masses of the lithium source, manganese source, iron source, and phosphorus source.
[0034] In some embodiments, the grinding in step S2 is first ball milling treatment using a ball mill and then sand milling treatment using a sand mill. The sand milling process is: sand milling using zirconia balls, the mass ratio of zirconia balls, material and water is (8-10):1:(1-1.5), the speed of the sand mill is 2000r / min, the time is 30-120min, and the particle size D50 after grinding is 1-15μm.
[0035] In some embodiments, the spray drying in step S2 includes one or both of centrifugal spray drying or two-fluid spray drying, and the spray drying process is: the feed inlet temperature is 200-260°C, the discharge port temperature is 90-130°C, the drying pressure is 0.1-0.5MPa, and the drying temperature is 150-400°C.
[0036] In some embodiments, the carbon source in step S3 includes at least one of glucose, sucrose, polyethylene glycol, citric acid, starch, ascorbic acid, cyclodextrin, and phenolic resin, and the amount of carbon source added is 0wt% to 10wt% of the sum of the mass of lithium source, manganese source, iron source, and phosphorus source; the calcination in S3 is a two-stage calcination, and the conditions for the first stage calcination are: temperature 250-450°C, time 2-6h; second stage calcination temperature 450-650°C, time 3-8h; the calcination atmosphere is an inert atmosphere, and the calcination heating rate is 2-10°C / min.
[0037] In the second aspect, a secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method described in the first aspect is provided, with a molecular formula of LiMnxFe1-xPO4 / C (x=0.4, 0.45, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9), a particle size D50 of 1μm-15μm, and is formed by the agglomeration of nanoscale primary particles.
[0038] In a third aspect, a lithium manganese iron phosphate battery is provided, comprising the secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method of the first aspect, or the secondary particle lithium manganese iron phosphate positive electrode material of the second aspect.
[0039] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0040] Embodiment 1:
[0041] A method for preparing a secondary particle lithium manganese iron phosphate positive electrode material, the steps are as follows:
[0042] S1, prepare lithium manganese iron phosphate slurry: dissolve 240g manganese sulfate, 242g iron sulfate, 366g ammonium dihydrogen phosphate, 210g lithium acetate, 100g citric acid, 5g carbon nanotube conductive material and 5g lithium aluminum silicate fast ion conductor material in 700g deionized water, and stir to obtain a composite slurry, wherein the element molar ratio of lithium manganese iron phosphorus and oxygen in the added raw materials satisfies 1:0.5:0.5:1:4.
[0043] S2, drying treatment: spray-dry the composite material slurry into a mixing tank, the spray-drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0044] S3, calcination treatment: the nanocomposite material obtained in S2 was mixed evenly with 80g of glucose, sintered at 700°C in a nitrogen atmosphere for 10h, and then sieved after cooling in the furnace to obtain secondary granular lithium iron manganese phosphate positive electrode material 1#LiMn 0.5 Fe 0.5 PO4 / C.
[0045] The crystal structure of the secondary particle lithium manganese iron phosphate positive electrode material prepared in Example 1 was analyzed using a Rigaku B / Max-2400 X-ray diffractometer. The results are as follows: Figure 1 As shown in the figure, it can be found that the diffraction peak of the secondary particle lithium manganese iron phosphate positive electrode material prepared by the present method is consistent with the peak type of the standard card (JCPDS No.33-0804), belongs to the orthorhombic crystal system, the space group is Pmnb (62), and there is no impurity phase. This further indicates that the positive electrode material modification technology of the present invention is a very mild technology and will not affect the bulk structure of the material. Figure 2 This is a scanning electron microscope image of the prepared secondary particle lithium manganese iron phosphate positive electrode material. It can be seen that the lithium manganese iron phosphate is a spherical secondary particle, which is formed by the agglomeration of nano-scale primary particles.
[0046] Embodiment 2:
[0047] A method for preparing a secondary particle manganese iron phosphate lithium positive electrode material. The difference between this embodiment and embodiment 1 is that different manganese sources, iron sources, phosphorus sources and lithium sources are used, and different carbon sources and sintering atmospheres are used during the sintering process. The steps are as follows:
[0048] S1, prepare lithium iron manganese phosphate slurry: add 344g manganese carbonate, 310g iron phosphate, 355g phosphoric acid (85%), 193g lithium carbonate, 8g polyethylene glycol, 10g aluminum-doped zinc oxide conductive material and 10g lithium aluminum titanium phosphate fast ion conductor material, and 2300g deionized water into a sand mill for sand grinding, wherein the iron phosphate has a particle size D50 of 1μm, the diameter of the zirconium oxide ball in the sand mill is 0.3mm, the mass ratio of the zirconium oxide ball to the material is 10:1, and the speed of the sand mill is 2200r / min. After grinding for 40min, a nano-scale composite slurry is obtained.
[0049] S2, drying treatment: adding the obtained composite slurry into a spray drying mixing tank for drying treatment, the spray drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0050] S3, calcination treatment: the nanocomposite material obtained in S2 and 120g sucrose were sintered at 700°C in an argon atmosphere containing 5% hydrogen for 8h, and then sieved after being cooled in the furnace to obtain secondary granular lithium manganese iron phosphate positive electrode material 2#LiMn 0.6 Fe 0.4 PO4 / C.
[0051] Embodiment 3:
[0052] A method for preparing a secondary particle lithium manganese iron phosphate positive electrode material. The difference between this embodiment and embodiment 1 is that different conductive materials and fast ion conductor materials are added. The steps are as follows:
[0053] S1, prepare lithium iron manganese phosphate slurry: add 344g manganese carbonate, 310g iron phosphate, 355g phosphoric acid (85%), 193g lithium carbonate, 8g polyethylene glycol, 10g fluorine-doped tin dioxide conductive material and 10g lithium aluminum titanium phosphate fast ion conductor material, and 2300g deionized water into a sand mill for sand grinding, wherein the iron phosphate has a particle size D50 of 5μm, the diameter of the zirconium oxide ball in the sand mill is 0.3mm, the mass ratio of the zirconium oxide ball to the material is 10:1, and the speed of the sand mill is 2200r / min. After grinding for 40min, a nano-scale composite slurry is obtained.
[0054] S2, drying treatment: adding the obtained composite slurry into a spray drying mixing tank for drying treatment, the spray drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0055] S3, calcination treatment: the nanocomposite material obtained in the previous step and 120g of glucose were sintered at 680°C in a nitrogen atmosphere for 8h, and then sieved after cooling in the furnace to obtain the secondary particle lithium manganese iron phosphate positive electrode material 3#LiMn 0.6 Fe 0.4 PO4 / C.
[0056] Embodiment 4:
[0057] A method for preparing a secondary particle lithium manganese iron phosphate positive electrode material. The difference between this embodiment and embodiment 1 is that different conductive materials and fast ion conductor materials are added. The steps are as follows:
[0058] S1, prepare lithium iron manganese phosphate slurry: add 320g manganese tetraoxide, 434g iron phosphate, 469g ammonium dihydrogen phosphate, 270g lithium carbonate, 8g polyethylene glycol, 15g antimony-doped tin dioxide conductive material and 15g lithium phosphorus oxygen nitrogen fast ion conductor material, and 2700g deionized water into a sand mill for sand milling, wherein the iron phosphate has a particle size D50 of 5μm, the diameter of the zirconium oxide ball in the sand mill is 0.3mm, the mass ratio of the zirconium oxide ball to the material is 10:1, and the speed of the sand mill is 2200r / min. After grinding for 60min, a nano-scale composite slurry is obtained.
[0059] S2, drying treatment: adding the obtained composite slurry into a spray drying mixing tank for drying treatment, the spray drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0060] S3, calcination treatment: the nanocomposite material obtained in the previous step and 80g of phenolic resin were sintered at 700°C in a nitrogen atmosphere for 8h, and then sieved after cooling in the furnace to obtain secondary particles of lithium iron manganese phosphate positive electrode material 4#LiMn 0.6 Fe 0.4 PO4 / C.
[0061] Embodiment 5:
[0062] A method for preparing a secondary particle manganese iron phosphate lithium positive electrode material. The difference between this embodiment and embodiment 1 is that different manganese sources, iron sources, phosphorus sources and lithium sources are used, and different conductive materials and fast ion conductor materials are added. The steps are as follows:
[0063] S1, prepare lithium iron manganese phosphate slurry: 320g manganese tetraoxide, 434g iron phosphate, 469g ammonium dihydrogen phosphate, 270g lithium carbonate, 8g polyethylene glycol, 8g graphene conductive material and 10g lithium aluminate fast ion conductor material, 2700g deionized water are added to a sand mill for sand grinding, wherein the iron phosphate has a particle size D50 of 5μm, the diameter of the zirconium oxide ball in the sand mill is 0.3mm, the mass ratio of the zirconium oxide ball to the material is 10:1, and the speed of the sand mill is 2200r / min. After grinding for 60min, a nano-scale composite slurry is obtained.
[0064] S2, drying treatment: adding the obtained composite slurry into a spray drying mixing tank for drying treatment, the spray drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0065] S3, calcination treatment: the nanocomposite material obtained in the previous step and 80g of phenolic resin were sintered at 700°C in a nitrogen atmosphere containing 5% hydrogen for 8h, and then sieved after cooling in the furnace to obtain secondary particles of lithium iron manganese phosphate positive electrode material 5#LiMn 0.6 Fe 0.4 PO4 / C.
[0066] Comparative Example 1:
[0067] A method for preparing a lithium manganese iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that no conductive material and fast ion conductor material are added, and the sintered material is subjected to air flow milling. The steps are as follows:
[0068] S1, prepare a mixed solution: add 320g manganese tetraoxide, 434g iron phosphate, 469g ammonium dihydrogen phosphate, 270g lithium carbonate, 8g polyethylene glycol, and 2700g deionized water into a sand mill for sand grinding, wherein the iron phosphate has a particle size D50 of 5 μm, the diameter of the zirconium oxide balls in the sand mill is 0.3mm, the mass ratio of the zirconium oxide balls to the materials is 10:1, and the speed of the sand mill is 2200r / min. After grinding for 60min, a composite slurry is obtained.
[0069] S2, drying treatment: adding the obtained composite slurry into a spray drying mixing tank for drying treatment, the spray drying pressure is 0.3 MPa, and the temperature is 300° C. to obtain a nano-composite material.
[0070] S3, calcination treatment: the nanocomposite material obtained in the previous step and 120g of glucose were sintered at 700°C in a nitrogen atmosphere for 8h, and then cooled in the furnace and crushed by a jet mill to obtain lithium manganese iron phosphate positive electrode material 6#.
[0071] Test example:
[0072] 1. Performance testing:
[0073] The secondary particle lithium manganese iron phosphate positive electrode materials of Examples 1-5 and Comparative Example 1 of the present invention are made into button batteries, and the gram capacity of the lithium manganese iron phosphate in Examples 1-5 and Comparative Example 1 is measured by button battery test. The preparation and testing methods of the button batteries are as follows:
[0074] NMP was used as solvent, and a slurry with a solid content of 60% was prepared according to the active material: SP: PVDF = 80: 10: 10 and evenly coated on aluminum foil to make the positive electrode. The negative electrode used a metal lithium sheet with a diameter of 17mm, and the electrolyte used 1mo1LiFP6 (EC: DEC: EMC = 1: 1: 1, V / V). The battery was packaged in the order of negative electrode shell-spring-gasket-lithium sheet-electrolyte-diaphragm-positive electrode sheet-gasket-positive electrode shell. The whole process was completed in an argon-filled glove box. The electrical performance test was carried out at a test temperature of 25°C. The battery capacity test method was: charging in a constant current and constant voltage charging mode, the limiting current was 0.1C (17mA / g), and the termination voltage was 4.2V: discharging in a constant current discharge mode, the discharge current was 1C (170mA / g), and the discharge cut-off voltage was 2.5V. The test results are shown in Table 1.
[0075] Table 1 Test results of button cells made of positive electrode materials in Examples 1-5 and Comparative Example 1
[0076] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 0.1C Gram Capacity (mAh / g) 152.5 152.0 151.5 151.3 150.1 135.1 1C gram capacity (mAh / g) 138.6 134.1 133.5 133.1 132.1 110.5 <![CDATA[Tap density (g / cm 3 )]]> 2.2 2.15 2.05 2.2 2 1.52
[0077] It can be seen from the experimental results in Table 1 that the tap density of the secondary particles of lithium manganese iron phosphate prepared by the method of the present invention is significantly improved and is basically maintained at 2-2.2 g / cm in Examples 1-5. 3, and the tap density in Examples 1-5 is significantly higher than that in Comparative Example 1. It can be seen that the batteries made of secondary particles of lithium manganese iron phosphate in Examples 1-5 with high tap density have a gram capacity greater than 150 mAh / g at 0.1C rate; it can be seen that the electrochemical performance in Examples 1-5 is better than that in Comparative Example 1. Therefore, the secondary particles of lithium manganese iron phosphate positive electrode materials prepared by various preparation methods in the present invention can make lithium manganese iron phosphate, conductive oxides and fast ion conductor materials work together to fully play their roles, while improving the problem of low electronic conductivity of lithium manganese iron phosphate, improving the tap density of lithium manganese iron phosphate materials, achieving better construction of electronic and ion channels, and improving its electrochemical performance.
[0078] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0079] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a secondary particle lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1, mixing a lithium source, an iron source, a manganese source, a phosphorus source and a dispersant to obtain a first mixed slurry; S2, mixing the first mixed slurry with the conductive material and the fast ion conductor, adding water, grinding, and spray drying to obtain a spherical precursor; S3, adding the spherical precursor to a carbon source for calcination and sieving to obtain a secondary particle manganese iron phosphate lithium positive electrode material.
2. The preparation method according to claim 1, characterized in that: The lithium source package in step S1 is a combination of at least one or more of lithium hydroxide, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate and dilithium hydrogen phosphate; the iron source includes a combination of at least one or more of iron phosphate, iron sulfate, iron nitrate, iron oxalate and iron acetate; the manganese source includes a combination of at least one or more of manganese phosphate, manganese sulfate, manganese nitrate, manganese oxalate and manganese acetate; the phosphorus source includes a combination of at least one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and dilithium hydrogen phosphate.
3. The preparation method according to claim 1, characterized in that: The conductive material in step S1 is a lamellar, rod-shaped, tubular or granular material of at least one or more combinations of graphite, graphene, carbon nanotubes, aluminum-doped zinc oxide, fluorine-doped tin dioxide and antimony-doped tin dioxide; the fast ion conductor material is a lamellar, rod-shaped, tubular or granular material of at least one or more combinations of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium phosphate, lithium aluminum silicate, lithium phosphorus oxygen nitrogen, sodium fast ion conductor material and lithium aluminate.
4. The preparation method according to claim 1, characterized in that: The dispersant in step S1 is a combination of one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol and citric acid, and the amount of the dispersant added is 1wt% to 20wt% of the sum of the mass of the lithium source, manganese source, iron source and phosphorus source; the element molar ratio of the raw material added in step S1 is lithium: manganese: iron: phosphorus: oxygen = 1: x: (1-x): 1: 4, 0.4 <x<1。 5. The preparation method according to claim 1, characterized in that: The mass of the conductive material in step S2 is 0.1wt% to 2wt% of the sum of the masses of the lithium source, manganese source, iron source and phosphorus source, and the mass of the fast ion conductor is 0.1wt% to 2wt% of the sum of the masses of the lithium source, manganese source, iron source and phosphorus source.
6. The preparation method according to claim 1, characterized in that: The grinding in step S2 is first ball milling, and then sand milling. The sand milling process is: using zirconia balls for sand milling, the mass ratio of zirconia balls, material and water is (8-10): 1: (1-1.5), the speed of the sand mill is 2000r / min, the time is 30-120min, and the particle size D50 after grinding is 1-15μm.
7. The preparation method according to claim 1, characterized in that: The spray drying in step S2 includes one or both of centrifugal spray drying or two-fluid spray drying, and the spray drying process is: the feed inlet temperature is 200-260°C, the discharge port temperature is 90-130°C, the drying pressure is 0.1-0.5MPa, and the drying temperature is 150-400°C.
8. The preparation method according to claim 1, characterized in that: The carbon source in step S3 includes at least one of glucose, sucrose, polyethylene glycol, citric acid, starch, ascorbic acid, cyclodextrin, and phenolic resin, and the amount of carbon source added is 0wt% to 10wt% of the sum of the mass of lithium source, manganese source, iron source, and phosphorus source; the calcination in S3 is a two-stage calcination, and the conditions for the first stage calcination are: temperature 250-450°C, time 2-6h; second stage calcination temperature 450-650°C, time 3-8h; the calcination atmosphere is an inert atmosphere, and the calcination heating rate is 2-10°C / min.
9. A secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The molecular formula is LiMn x Fe 1-x PO4 / C (x=0.4, 0.45, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9), particle size D50 is 1μm-15μm, and is formed by the agglomeration of nanoscale primary particles.
10. A lithium manganese iron phosphate battery, characterized in that: It comprises the secondary particle lithium manganese iron phosphate positive electrode material obtained by the preparation method described in any one of claims 1 to 8, or the secondary particle lithium manganese iron phosphate positive electrode material described in claim 9.
Citation Information
Cited By
Lithium manganese iron phosphate positive electrode material, preparation method and pure power battery
CN121331804A
